FACTORS AFFECTING PREGNANT WOMEN'S KNOWLEDGE LEVEL OF PREECLAMPSIA SCREENING - Fatharani, Salwa; Andriyanti; Ernawati; Atika (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Preeclampsia is a hypertensive syndrome affecting 3–8% of pregnancies worldwide, involving multiple organ systems, and typically occurring after 20 weeks of gestation. In Surabaya, 1,265 cases were reported in 2023. Optimal prevention of preeclampsia is achieved through early screening at 11–13 weeks of gestation during antenatal care. Maternal knowledge and awareness are essential determinants of timely screening, as non-adherence to antenatal care has been associated with insufficient understanding of pregnancy management, delayed recognition of complications including preeclampsia and chronic conditions, and has ultimately contributed to the persistently high rates of preeclampsia and maternal and neonatal mortality in Indonesia. The aim was to analyze factors influencing pregnant women’s knowledge regarding preeclampsia screening. Method: This research employed a quantitative design with a cross-sectional approach, using a purposive sampling method. This study involved 91 pregnant women who met the inclusion criteria: women in the first to third trimester of pregnancy who had attended at least two antenatal care visits. A structured questionnaire was used as the research instrument. Data were analyzed using the Spearman rank correlation test to examine the relationship between educational level and parity experience and the pregnant women’s level of knowledge regarding preeclampsia screening. Results: The study included 91 pregnant women as respondents. 56 % respondent had secondary level of education, 52% respondents were moderate parity and 52 % respondents demonstrated good knowledge, Showed significant associations between education level (p < 0.001) and parity (p = 0.031) with knowledge of preeclampsia screening. Conclusions: That demographic factors and reproductive experiences influence maternal knowledge. Therefore, education on preeclampsia screening should be tailored to maternal characteristics, and the active involvement of healthcare providers is essential to support comprehensive, holistic, and sustainable midwifery care.